Median levels of serum biomarkers of fetal Down syndrome detected during the first trimester among pregnant Thai women - Luewan S. (2014)
Objective: To develop Thai-specific medians of serum pregnancy-associated plasma protein A (PAPP-A) and free β-human chorionic gonadotropin (hCG) levels during the first trimester of pregnancy and to compare these values to a Caucasian-specific model for the detection of fetal Down syndrome. Methods: Serum concentrations of PAPP-A and free β-hCG were measured during the first trimester in a group of 2339 Thai women undergoing normal singleton pregnancies. Results: Thai reference ranges of PAPP-A and free β-hCG were established by gestational age (70-98 days). The equation of best fit for PAPP-A was: predicted median PAPP-A level = 28.767 - 0.781 × (gestational age in days) + 0.006 × (gestational age in days) 2; r = 0.986. The equation of best fit for free β-hCG was: predicted median free β-hCG level = 465.332 × 10 (-0.024 × gestational age in days); r = 0.881. Weight-corrected models were also derived for each biomarker. The Thai-specific reference ranges gave higher positive screening rates than the Caucasian-specific model, even after weight correction (5.1% versus 4.0%). The Thai-specific models were validated in an independent group of 302 pregnant women. Conclusion: Ethnic group-specific medians for PAPP-A and free β-hCG should be incorporated during first-trimester screening for fetal Down syndrome. © 2012 International Federation of Gynecology and Obstetrics.